The Impact of Social and Emotional Learning on Student Wellness (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Social and Emotional Learning (SEL) is a critical component of education that focuses on developing students' emotional intelligence, social skills, and self-awareness. This paper explores the impact of SEL on student well-being, examining how SEL programs foster emotional regulation, social skills, self-efficacy, and academic performance. Through a review of existing literature, the paper highlights the significant benefits of SEL, including improved mental health, reduced behavioral problems, and enhanced academic outcomes. Case studies from various educational settings demonstrate the practical application of SEL and its positive effects on students. The paper concludes with recommendations for educators and future research directions, emphasizing the need for widespread implementation of SEL to support holistic student development.